Current status of early childhood education teachers' professional competencies in response to the implementation of the competency-based early childhood education curriculum in Vietnam - Ha, Nguyen Thi Thu; Trang, Nguyen Thi; Minh, Vu Thi Ngoc; Bich, Nguyen Thi Cam; Trinh, Nguyen Thi My; Giang, Vu Thi Huong (Edelweiss Applied Science and Technology, 2025)
This study examines the professional competencies of early childhood education (ECE) teachers in Vietnam in response to the implementation of a competency-based ECE curriculum. Employing a mixed-methods approach, the research included a survey of 329 ECE teachers using structured questionnaires, observations of 62 educational activities across public and private ECE institutions in two socioeconomically distinct regions, and semi-structured interviews with 12 administrators and 40 teachers. Results revealed that while most teachers self-assessed their competencies as proficient, particularly in cognitive competence and professional attitudes, classroom observations, discussions, and interviews disclosed significant limitations in practical teaching skills. These gaps were evident in teachers' ability to adapt lesson plans based on assessment data, respond to individual children's needs, including those with disabilities and special needs, provide effective feedback, and integrate technology meaningfully into instruction. Disparities in teacher competencies across regions and institution types reflected variations in working conditions and professional development opportunities. These findings provide empirical evidence to inform the development of a national competency framework for early childhood teachers, guide policy formulation, and enhance teacher preparation programs to support the effective implementation of Vietnam's competency-based ECE curriculum during the next phase of educational reform.